Harnessing Natural Pozzolan for Sustainable Heating and Cooling: Thermal Performance and Building Efficiency in Moroccan Climates - Khadija Annaba; Sara Belarouf; Fatima Zohra El Wardi; Khalid Ibaaz; Mouha Cherkaoui; Céline Florence; Johan Colin; Romain Mege; Yassine El Mendili (Buildings, 2024)
The need to construct environmentally friendly buildings to meet current environmental and ecological standards is urgent. This study introduces a new multi-layer construction material with two outer layers of ordinary mortar and an inner layer of a pozzolane-limes composite to meet this need. The thermal efficiency of this material in building construction is investigated using TRNSYS18 simulations for two distinct climatic zones in Morocco, with a particular focus on its impact on heating dynamics. The primary objective is to evaluate the thermal performance of multi-layered pozzolanic materials, for which mortar samples are meticulously prepared as a reference in the two different climatic zones (Azilal and Errachidia). Using the asymmetric hot plate method under both stable and transient conditions, the authors conduct thermal characterization experiments. The results underscore the improvement in thermal performance made possible by the incorporation of pozzolan as an aggregate in the multi-layer material compared to ordinary mortar. Specifically, thermal conductivity improves significantly, from 0.735 W m−1 K−1 for ordinary mortar to 0.4 W m−1 K−1 for multi-layered pozzolanic materials, representing a 46% mass gain. Additionally, effusivity decreases from 730 to 604 J m−2 K−1 s−1/2, while diffusivity decreases from 3.78 to 2.23 × 10−7 m2 s−1, further attesting to the material’s thermal efficacy. TRNSYS18 simulations corroborate the viability of using multi-layered materials as building envelopes, revealing potential annual heating gains of 25% in Azilal and 5% in Errachidia. These findings underscore the promising prospects of integrating these materials into sustainable construction practices.